2007
DOI: 10.1038/modpathol.3800700
|View full text |Cite
|
Sign up to set email alerts
|

Expression of GalNAc-T3 and its relationships with clinicopathological factors in 61 extrahepatic bile duct carcinomas analyzed using stepwise sections—Special reference to its association with lymph node metastases—

Abstract: Extrahepatic bile duct carcinomas (EBDCs) still result in an unfavorable prognostic outcome, and little is known about their biological aggressiveness. Recently, UDP-N-acetyl-alpha-D-galactosamine:polypeptide N-acetylgalactosaminyl transferase-3 (GalNAc-T3) was reported to be associated with differentiation and malignant potential of human carcinomas. Here, we investigated 61 EBDCs for their detailed clinicopathological features and GalNAc-T3 expression by immunohistochemistry, and then evaluated the relations… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
10
0

Year Published

2008
2008
2021
2021

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 20 publications
(11 citation statements)
references
References 26 publications
(41 reference statements)
1
10
0
Order By: Relevance
“…In addition, our results also showed a particular association of venous invasion with ppGalNAc-T6 expression in tumors localized in the body region of the stomach. Different levels of ppGalNAc-T3 have been detected in patients with various types of carcinomas (Shibao et al 2002;Gu et al 2004;Ishikawa et al 2004;Miyahara et al 2004;Yamamoto et al 2004;Landers et al 2005;Inoue et al 2007), and this has been associated with a poor prognosis. ppGalNAc-T6 exhibits a high sequence homology to ppGalNAc-T3, and in vitro studies have shown that both enzymes display similar acceptor substrate specificities (Bennett et al 1999b).…”
Section: Discussionmentioning
confidence: 99%
“…In addition, our results also showed a particular association of venous invasion with ppGalNAc-T6 expression in tumors localized in the body region of the stomach. Different levels of ppGalNAc-T3 have been detected in patients with various types of carcinomas (Shibao et al 2002;Gu et al 2004;Ishikawa et al 2004;Miyahara et al 2004;Yamamoto et al 2004;Landers et al 2005;Inoue et al 2007), and this has been associated with a poor prognosis. ppGalNAc-T6 exhibits a high sequence homology to ppGalNAc-T3, and in vitro studies have shown that both enzymes display similar acceptor substrate specificities (Bennett et al 1999b).…”
Section: Discussionmentioning
confidence: 99%
“…Higher expression of GalNAc-T1, GalNAc-T2 and GalNAc-T3 has also been described in colorectal carcinoma when compared with the normal colonic epithelium [27]. Different levels of expression of GalNAc-T3 were detected in patients with colorectal [12], lung [28], pancreatic [29], gastric [30], gallbladder [31], prostate [32] and extrahepatic bile duct carcinomas [33], and it was identified as an independent factor of prognosis. GalNAc-T6, which exhibits a high sequence homology to GalNAc-T3, has been recently described to be expressed in most ductal breast carcinomas but not in normal breast epithelium.…”
Section: Introductionmentioning
confidence: 99%
“…GalNAc-T3 and GalNAc-T6 display high similarity at both DNA and amino acid levels, having similar genomic organization with nine identically positioned intron/exon boundaries in the coding regions (10). GalNAc-T3 is expressed in almost all normal epithelia, and dysregulated expression of GalNAc-T3 has been observed in various carcinomas, including oral (41,47), colon (44), pancreatic (48 -50), breast (51), gallbladder (52), gastric (53,54), prostate (55), renal (56), lung (57), esophageal (58), thyroid (59), and extrahepatic bile duct (42) carcinomas. GalNAc-T6 is also reported to be aberrantly expressed in various types of cancer, including breast (60 -64), gastric (40), renal (56), and pancreatic (49) carcinomas.…”
mentioning
confidence: 99%